MIR1183 as a new tissue biomarker with triggered acute response and upregulation in chronic atrial and ventricular remodeling. (25th November 2020) - Djalinac, N; Kolesnik, E; Maechler, H; Sedej, S; Rainer, P; Scher, D; Heinemann, A; Von Lewinski, D; Bisping, E
Abstract: Background and purpose: Cardiac remodeling can be caused by a variety of insults linked to either stretch or tachycardia as a triggering mechanism. We aimed to investigate similarities and differences of the transcriptomic profiles in response to either acute stretch or tachycardia in isolated human atrial myocardium. In addition, we tested the highest acutely regulated target for its chronic regulation in human tissue with atrial or ventricular cardiac remodeling. Methods: For acute trigger testing we applied either stretch (high pre- and afterload) or sustained tachycardia (2.5 Hz) for 6 hours in isolated atrial human trabeculae from cardiac surgery patients (all in sinus rhythm, SR). We performed gene expression profiling by RNA microarrays (n=5 per group) as a remodeling readout. For chronic regulation we performed qPCR of selected genes of interest in right atrial appendage tissue obtained from cardiac surgery patients with persistent atrial fibrillation compared to control patients with SR (n=6 per group), and also in ventricular tissue samples from failing hearts (from transplanted dilative cardiomyopathy patients) or non-failing control hearts (from multi-organ donors denied for transplantation), n=6 per group. Results: The expression patterns of stretch and tachycardia were largely independent with 1305 transcripts regulated solely by stretch and 1837 transcripts by tachycardia with p<0.05. In contrast, the fraction of commonly regulated genes was small (65 transcripts with p<0.05). However, this fraction contained the strongest upregulated transcript, the microRNA precursor gene MIR1183, which was similarly upregulated by both triggers (4.1fold in stretch and 2.7fold in tachycardia, both p<0.05). MIR1183 also showed upregulation in two important chronic remodeling settings: In atrial samples with persistent atrial fibrillation in comparison to sinus rhythm, it was 2.8fold upregulated, and in ventricular samples from dilative cardiomyopathy hearts it was 1.6fold upregulated (p<0.05 for both). A functional role of MIR1183 in remodeling was also suggested by significant downregulation of its predicted downstream target genes ADAM20 and PLA2G7. Our ongoing research aims to confirm upregulation also in the circulating expression levels of the mature form of MIR1183 in human plasma samples in a cohort of atrial fibrillation patients with diseased atria, these findings will also be presented at scientific sessions. Conclusion: Stretch and tachycardia show distinct transcriptomic signatures in human atrial trabeculae but share the strongest upregulated gene MIR1183 and consistent regulation of its downstream targets. This is present in an acute as well as chronic remodeling setting. Expression levels of MIR1183 might serve as a biomarker for atrial remodeling and to some extend ventricular remodeling and have potential functional significance in cardiac disease. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Medical University of Graz